Cfd Simulation Study of The Novel Multistage Inlet Gasifier For Enhancement of Syngas Production - Rosli, Muhammad Irfan; Samiran, Nor Afzanizam (Progress in Engineering Application and Technology, 2022)
Economically, fossil fuels remain the main source of energy despite theirhigh emissions of greenhouse gases. However, biomass, a renewable fuel with CO2neutrality, has experienced widespread attention as a potential contributor to thesustainable development of the energy sector. Gasification is an importantthermochemical process that converts biomass feedstock into H2-rich combustiblegases known as syngas. Its main product (syngas) can be used as fuel in variousconversion technologies to produce different products, including electricity andchemicals. This research study focuses particularly on biomass gasification that is apromising technology to achieve high-quality syngas in the presence of one or moregasification agents. To accomplish this aim, a single-stage and two-stage downdraftreactor are analysed in this study using an equilibrium model with non-premixedcombustion in the ANSYS Fluent. This study shows that the CFD model simulatedvalues of outlet gas composition was in good agreement and was validated with thePaul1 model prediction and experimental data2. The highest temperature inside thegasifier for a single stage model is found in the oxidation zone, where the air issupplied. The temperature in the drying zone is less than 460K, in the pyrolysis zoneis between 470 and 455K, in the oxidation zone is between 470 and 490K, and in thereduction zone is between 480 and 485K. The highest temperature inside the gasifierfor a double stage model is found in the oxidation zone, where the air is supplied. Thetemperature in the drying zone is less than 470K, in the pyrolysis zone is between 470and 480K, in the oxidation zone is between 470 and 520K, and in the reduction zoneis between 480 and 485K. It is observe that the CO and H2 concentrations are higherin the pyrolysis zone for single and double stage as the volatile matter turn to gasesphase due devolatilization process. Then for CH4 mole fraction, the single stage was0.06% while the double stage was 0.03%.3 reported CH4 values similar to those foundin this study. It is demonstrated the advantages of the double stage by supply air ingasification experiments in a downdraft gasifier.